Chinggis Khan’s Vision of World Rule, and How it Remade China - Man, John (Mongolian Journal of International Affairs, 2013)
DOI: http://dx.doi.org/10.5564/mjia.v0i17.84 Mongolian Journal of International Affairs, No.17 2012: 81-84